Global Optogenetic Activation of Inhibitory Interneurons during Epileptiform Activity - Ledri, Marco (J Neurosci, 2014)
Optogenetic techniques provide powerful tools for bidirectional control of neuronal activity and investigating alterations occurring in excitability disorders, such as epilepsy. In particular, the possibility to specifically activate by light-determined interneuron populations expressing channelrhodopsin-2 provides an unprecedented opportunity of exploring their contribution to physiological and pathological network activity. There are several subclasses of interneurons in cortical areas with different functional connectivity to the principal neurons (e.g., targeting their perisomatic or dendritic compartments). Therefore, one could optogenetically activate specific or a mixed population of interneurons and dissect their selective or concerted inhibitory action on principal cells. We chose to explore a conceptually novel strategy involving simultaneous activation of mixed populations of interneurons by optogenetics and study their impact on ongoing epileptiform activity in mouse acute hippocampal slices. Here we demonstrate that such approach results in a brief initial action potential discharge in CA3 pyramidal neurons, followed by prolonged suppression of ongoing epileptiform activity during light exposure. Such sequence of events was caused by massive light-induced release of GABA from ChR2-expressing interneurons. The inhibition of epileptiform activity was less pronounced if only parvalbumin- or somatostatin-expressing interneurons were activated by light. Our data suggest that global optogenetic activation of mixed interneuron populations is a more effective approach for development of novel therapeutic strategies for epilepsy, but the initial action potential generation in principal neurons needs to be taken in consideration.